Karakteristik Morfobiometrik Ayam Kampung Di Kecamatan Huamual Berdasarkan Jenis Kelamin Berbeda - Rajab Rajab; Wiesje M. Horhoruw; Fiki F. Samal (Jurnal Ilmu dan Industri Peternakan, 2022)
This research aim was to determine the morphometric characteristics of native chickens in the Huamual District. A total of 300 adult Kampung chickens (consisting of 150 males and 150 females) with more than 20 weeks of age were used as research samples. Analysis of qualitative traits by calculating proportions or percentages, where chickens were grouped by sex. Quantitative traits were analyzed using descriptive statistical analysis by calculating the mean, standard deviation, and coefficient of variance. In order to determine the relationship between body measurements (chest circumference, femur length, tibia length, shank length, shank circumference) and body weight of native chickens, a simple regression analysis method was used. The results showed that the qualitative traits of Kampung chickens were dominated by the color of the black plumage of the hen and the wild color of the male, white or yellow on the shank, and the form of a single comb. The average body weight of Kampong chicken was 1602.17 g, chest circumference 28.17 cm, femur length 14.96 cm, tibia length 10.71 cm, shank length 9.11 cm with a diameter of 5.01 cm in males, while females have an average body weight of 1083.75 g, chest circumference 23.37 cm, femur length 12.53 cm, tibia length 8.72 cm, shank length 8.23 with a diameter of 3.68 cm. Shank length can be used as the best and most appropriate measure to estimate the body weight of chickens, both male and female.